Introduction to the history of Christianity - Dowley, Tim; Briggs, John H. Y.; Linder, Robert Dean; Wright, David F. (England : Lion books, 2014)
"Combining the accuracy and readability of the first edition of this highly acclaimed text, Dowley has enhanced the second edition with new contributions from Pheme Perkins on 'The Thought-World of Early Christianity' and Richard Burridge on 'Jesus and the Gospels' as well as updated and revised contributions from Ward Gasque, Richard Pierard, John H.Y. Briggs, and more. With many new photographs, illustrations, maps, charts, and timelines, the inviting new full-color format tells the dramatic, intriguing, and often surprising story of Christians in their 2000-year journey to the present day. This textbook can be purchased individually or as part of a course pack which includes the Study Companion. Authoritative content, comprehensive scope, arresting four-color illustration, and innovative learning aids, now in multiple formats for complete versatility. Also available as an Inkling Interactive Textbook: the full content of the textbook PLUS!"--Publisher description.
pt. 1. Beginnings AD 1-325 -- 1. Jesus: his life, ministry, death and its consequences -- 2. The church begins: from Jerusalem to Rome -- 3. Establishing Christianity: challenges to the new faith -- 4. Spreading the good news: how and why Christianity expanded -- 5. Archaeology and earliest Christianity: what archaeologist can - and cannot - illuminate -- 6. What the first Christians believed: the faith is defined -- 7. How the first Christians worshipped -- pt. 2. Acceptance and Conquest: AD 325-600 -- 8. Constantine and the Christian Empire: Christianity recognized -- 9. Councils and Creeds: defining and defending the faith -- 10. Buildings and belief: early church structures -- 11. Worship and the Christian year: the making of the Christian calendar -- 12. Clergy, Bishops, and Pope: the church builds an organisation -- 13. The church in North Africa: the making of a distinctive tradition -- 14. The fall of the Roman Empire: how and why it came to an end -- 15. Ascetics and monks: the rise of Christian monasticism -- pt. 3. A Christian Society: AD 600-1500 -- 16. The West in crisis -- 17. The Eastern church -- 18. Flowering: the Western church: reform and resurgence -- 19. Monasticism in the West -- 20. The Orthodox church in Eastern Europe and Russia -- 21. An age of unrest: the Western church in the late middle ages -- pt. 4. Reform and renewal: 1500-1650 -- 22. Seeds of renewal: the origin of the Reformation -- 23. Reformation -- 24. A flood of bibles: scripture in the vernacular -- 25. The radical reformation: the Anabaptists -- 26. The Catholic Reformation -- 27. Art and the spirit: Christianity and its cultural expression -- pt. 5. Reason, revival, and revolution 1650-1789 -- 28. Expansion worldwide: European missions -- 29. Awakening: the Evangelical revival and the great awakening -- 30. Reason and unreason: the rise of rationalism -- 31. The Russian church: 1500-1900 -- pt. 6. Cities and Empires 1789-1914 -- 32. Europe in revolt: church and state in the nineteenth century -- 33. The first industrial nation: the industrial revolution and the British churches -- 34. A crusade among equals: revivalism, abolition, and evangelism in the USA -- 35. A world come of age: science and philosophy challenge Christianity -- 36. Outposts of empire: the nineteenth-century missionary explosion -- pt. 7. A Century of Conflict 1914-2001 -- 37. An age of ideology: nationalism, communism, and individualism take on Christianity -- 38. An age of anxiety: theological thinking in troubled era -- 39. Pentecostalism and the charismatic movement -- 40. The arts in the Christian West -- 41. Organizing for unity -- 42. An age of liberation -- pt. 8. Epilogue: A New Millennium -- 43. Present and future: the church in an ever-changing world.
"Original edition published as A Lion handbook: The history of Christianity, 1977"--Title page verso.
Includes bibliographical references and index.
Keywords: Church history